Deubiquitylation machinery is required for embryonic polarity in Caenorhabditis elegans. - Richard J McCloskey; Kenneth J Kemphues (PLoS Genetics, 2012)
The Caenorhabditis elegans one-cell embryo polarizes in response to a cue from the paternally donated centrosome and asymmetrically segregates cell fate determinants that direct the developmental program of the worm. We have found that genes encoding putative deubiquitylating enzymes (DUBs) are required for polarization of one-cell embryos. Maternal loss of the proteins MATH-33 and USP-47 leads to variable inability to correctly establish and maintain asymmetry as defined by posterior and anterior polarity proteins PAR-2 and PAR-3. The first observable defect is variable positioning of the centrosome with respect to the cell cortex and the male pronucleus. The severity of the polarity defects correlates with distance of the centrosome from the cortex. Furthermore, polarity defects can be bypassed by mutations that bring the centrosome in close proximity to the cortex. In addition we find that polarity and centrosome positioning defects can be suppressed by compromising protein turnover. We propose that the DUB activity of MATH-33 and USP-47 stabilizes one or more proteins required for association of the centrosome with the cortex. Because these DUBs are homologous to two members of a group of DUBs that act in fission yeast polarity, we tested additional members of that family and found that another C. elegans DUB gene, usp-46, also contributes to polarity. Our finding that deubiquitylating enzymes required for polarity in Schizosaccharomyces pombe are also required in C. elegans raises the possibility that these DUBs act through an evolutionarily conserved mechanism to control cell polarity.